The economics of recreation, leisure and tourism - Tribe, John (Abingdon, Oxon ; New York : Routledge, 2020)
"One of the leading texts in the field, The Economics of Recreation, Leisure and Tourism is the ideal introduction to the fundamentals of economics in these industries, helping you to enjoy and pass an economics module as part of tourism, recreation, events or sport management degrees. International in its outlook, it will equip you with vital skills and knowledge for your future career as well as critical skills to help you understand and help tackle crucial challenges facing the world. It is written in a clear and engaging style that assumes no prior knowledge of economics. It applies economic theory to a range of tourism industry issues at the consumer, business, national and international level by using topical examples to give the theory real-world context. This book is richly illustrated with diagrams and contains a range of features such as international case studies showcasing current issues, review questions and extracts from journals to aid understanding and further knowledge, as well as new data and statistics. It concludes with a powerful critique of traditional economics and a set of twenty-one issues that demand action. This sixth edition has been revised and updated to include: Recent and time series international economic data to provide a sense of the dynamics of world economies. Topical analysis to aid decision making for industry, governments and pressure groups. A renewed emphasis on environmental and climate change issues New and revised international case studies that demonstrate theoretical principles of economics as applied to the sector. Companion website with PowerPoint slides"--
Includes bibliographical references and index.
Keywords: Leisure -- Economic aspects; Recreation -- Economic aspects; Tourism; Recreation -- Marketing; Tourism -- Marketing; Leisure industry -- Finance; Tourism -- Finance